Investigating, Determining Morphological Features, Development and Producing Capacity, and Linking Local Rice (Oryza Sativa L.) in Sumedang District - Amalia, Lia; Sondari, Nunung; Komariah, Ai; Sukmawati, Deti; Ulfah, Indriana; Mulyana, Hudaya; Parlinah, Linlin; Hanan, Acep (Jurnal Agrosci, 2024)
In order to create future superior varieties, local rice (Oryza sativa L.) is a source of germplasm. In Sumengang Regency, conservation efforts are required to prevent the extinction of native rice genotypes. This study attempts to investigate native rice in Sumedang Regency, identifying morphological characteristics, studying growth and yield, and family links. The study's sites included greenhouses and experimental paddy fields at Winaya Mukti University's Faculty of Agriculture in Tanjungsari, Sumedang Regency, and the Sumedang Regency area. A survey method, descriptive qualitative analysis, and an experimental methodology employing a Randomized Block Design (RBD) with 18 treatments of local rice cultivars and two repetitions were used to conduct the research from May 2022 to December 2022. Sixteen local rice cultivars from Sumedang and two local rice cultivars from Tuban and Probolinggo were discovered as a result of research in the form of exploration; morphological characters were identified using the UPOV criteria (2020); growth characters with high yields were discovered in Gemah and Tri Sakti cultivars, whereas Bagendit cultivars tended to have low growth but high fruitfulness. All 18 of the examined cultivars showed variations in growth and yield. The dendrogram that resulted from the phenetic analysis split the eighteen rice cultivars into two groups: Group I was made up of local rice cultivars, namely Sertani, Bagendit, Masreum, Gading, Jablay, Patenggang, Gede Wangi, Hawara salak, Mentik Susu A, Godang, and Omas Genteng; group II was made up of local rice cultivars, namely Jalur, Gemah, Mesir Super, Sri Dewi, Tri Sakti, Mentik Susu B, and Mareum. There is a 56.16% similarity between each distinct rice variety. Many Sumedang local rice cultivars, such as Gading, Jablay, and Patenggang, share morphological characteristics. The morphological character data shows a 90% similarity coefficient amongst the cultivars.